The Fluoretec system for rapid diagnosis of bacteroides infections by direct immunofluorescence of clinical specimens. Issue 12 (December 1981) - Slack, M P; Griffiths, D T; Johnston, H H
Abstract : Fluoretec, a commercial kit for the rapid diagnosis by immunofluorescence of infections caused by Bacteroides spp was compared with a standard culture method. A total of 1010 specimens were tested for the presence of B fragilis group by Fluoretec F and B melaninogenicus-oralis and asaccharolytic groups by Fluoretec M. Fluoretec F was positive in 123/152 specimens culturing B fragilis group strains. Seventeen specimens were positive by Fluoretec F but negative on culture. Fluoretec M was positive in 21 of 22 specimens from which B melaninogenicus was cultured. The Fluoretec system was convenient in use, results being obtained within one hour of receipt of the specimen.